HUBUNGAN BUDAYA ORGANISASI DAN RESISTENSI PERUBAHAN DALAM TRANSFORMASI DIGITAL - Riduan Siagian; Parlaban Karo-Karo; Banpensyahputra (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Digital transformation has become essential for manufacturing companies to improve operational efficiency, innovation, and competitiveness, yet its implementation is frequently hindered by employee resistance rooted in cultural factors. This study aims to identify and analyze the relationship between organizational culture and resistance to change in the context of digital transformation, including resistance mechanisms such as competence anxiety, status loss, information overload, and fear of losing autonomy. The research employs a qualitative descriptive approach with a case study design in manufacturing firms undergoing digital transformation. Data were collected through in-depth interviews, questionnaires, and documentation/archival studies, and were analyzed using triangulation that integrates qualitative and quantitative findings. The results indicate a significant relationship between an adaptive and innovative organizational culture and a low level of resistance. Companies with a culture that supports innovation demonstrate higher technology adoption and better readiness, whereas hierarchical and rigid cultures tend to create uncertainty and resistance. The findings also highlight the critical roles of transparent communication and active leadership, supported by training and early employee involvement, as key strategies to reduce resistance. The study implies that organizations must manage and reshape their culture to create a more supportive work environment for adopting new technologies and to accelerate successful digital transformation.